ElizaE
contestada

please help! I will mark brainliest for correct answer and explanation! please and thank you in advance!

solve with elimination
9x – 8y = 4
2x – 3y = -4​

Respuesta :

Answer: Y = 4, X=4 (4,4)

Step-by-step explanation: You must multiply both equations so the leading coefficient cancels out. I’m multiplying both equations by both coefficients so I multiply the entire first equation by -2 so the first equation will be the negative coefficient and the second equation will be multiplied by positive 9 so the negative and positive equations cancel out.

STEPS IN MATH:

1. (9x-8y=4) -2 = -18x + 16y = -8

(2x-3y=-4)9 = 18x-27y= -36

2. ADD THESE EQUATIONS TOGETHER NOW

-18x+16y=-8

+ 18x-27y=-36

0-11y= -44

-11y=-44

DIVIDE -44 by -11y

The final answer is Y= 4

NOW pick an equation to plug in y to, any equation works

I chose the first one, so 9x-8(4)=4

9x-32=4

9x=36

x=4

Answer:

point form (4,4)

equation form  x= 4, y= 4

Step-by-step explanation: